P PENGARUH PROBLEM BASED LEARNING BERBANTUAN MEDIA CANVA TERHADAP MOTIVASI DAN PRESTASI BELAJAR IPAS KELAS V SDN 01 SUKADANA - Indriyani, Rina (FKIP UM Pontianak, 2026)
ABSTRACT This research aims to determine the effect of Problem Based Learning assisted by Canva media on the motivation and learning achievement of fifth-grade IPAS students at SDN 01 Sukadana, specifically on the water cycle material. This study employs a quantitative approach and a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects were 40 V grade students at SDN 01 Sukadana. Purposive sampling was used for the sample selection, where class VA was designated as the experimental group, receiving treatment using the Problem Based Learning model assisted by Canva media, while class VB served as the control group, receiving treatment using conventional/lecture-based learning. The instruments used were a learning motivation questionnaire and a student learning achievement test. The analysis employed in this study involved normality and homogeneity prerequisite tests, followed by Multivariate Analysis of Variance (MANOVA) using SPSS 22 to examine the effect of Canva-assisted Problem Based Learning on student motivation and learning achievement. The multivariate test results indicate that the learning model variable significantly influences student motivation and learning achievement (Sig. 0.000 < 0.05).